2019
DOI: 10.1039/c9ra03279g
|View full text |Cite
|
Sign up to set email alerts
|

Efficient detoxification of triclosan by a S–Ag/TiO2@g-C3N4hybrid photocatalyst: process optimization and bio-toxicity assessment

Abstract: Owing to their persistency and toxicity, development of an effective strategy to eliminate antibiotic residues from the aquatic system has become a major environmental concern.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
5
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 56 publications
2
5
0
Order By: Relevance
“…A hybrid structure with g-C3N4 acts as a good visible light active photocatalyst. S–Ag/TiO2@g-C3N4 is a hybrid catalyst that helps in triclosan (TS) detoxification and visible light degradation (Xie et al 2019 ). In the presence of boron carbonitride, polyaniline has several purposes, such as hydrogen generation detoxifying organic and inorganic pollutants by acting as a photocatalyst (Raghu et al 2021 ).…”
Section: Interactions Of Pollutants In the Environment Through Separa...mentioning
confidence: 99%
“…A hybrid structure with g-C3N4 acts as a good visible light active photocatalyst. S–Ag/TiO2@g-C3N4 is a hybrid catalyst that helps in triclosan (TS) detoxification and visible light degradation (Xie et al 2019 ). In the presence of boron carbonitride, polyaniline has several purposes, such as hydrogen generation detoxifying organic and inorganic pollutants by acting as a photocatalyst (Raghu et al 2021 ).…”
Section: Interactions Of Pollutants In the Environment Through Separa...mentioning
confidence: 99%
“…114 A significantly higher efficiency was reported for the sulfur-containing S/Ag-TiO 2 @g-C 3 N 4 material, which decreases the initial TCS concentration by approximately 92% under the above-mentioned conditions. 114 Chang et al reported the photoinduced decomposition of a higher concentrated TCS solution (β = 20 mg•L −1 ) in the presence of the bismuth(III) oxide iodide composite Bi 7 O 9 I 3 /Bi 5 O 7 I (β = 1.0 g•L −1 ) under simulated solar light irradiation (xenon lamp, P = 500 W), and approximately 10% of the initial TCS concentration remained after illumination for 150 min. 115 The efficiency of Bi 7 O 9 I 3 /Bi 5 O 7 I is concluded to be equal to that of BiCeO-a, which was used for the photocatalytic decomposition of a TCS solution of lower concentration (β = 10 mg• L −1 ) in the presence of a lower catalyst loading (β = 0.25 g• L −1 ); both systems provide similar rate constants for the decomposition (Bi 7 O 9 I 3 /Bi 5 O 7 I, k = 0.017 min −1 ; BiCeO-a, k = 0.026 min −1 ).…”
Section: ■ Discussionmentioning
confidence: 90%
“…The results obtained from the preliminary decomposition experiments of TCS in the presence of visible-light-driven β-Bi 2 O 3 :Ce were compared to “state-of-the-art” catalyst systems, which were reported using similar conditions. In the presence of BiCeO-a particles (β = 0.25 g·L –1 ), the initial TCS concentration (β = 11 mg·L –1 ) was reduced by approximately 80% after illumination for 60 min (xenon lamp, P = 300 W, 420 nm ≤ λ ≤ 700 nm), thus indicating a higher efficiency compared to TiO 2 @g-C 3 N 4 and Ag-TiO 2 @g-C 3 N 4 composites (β = 0.2 g·L –1 ) in the photocatalytic decomposition of TCS (β = 10 mg·L –1 ) under visible-light irradiation (xenon lamp, P = 250 W, λ ≥ 420 nm) for 60 min, with decreases by approximately 25% and 50% of the initial TCS concentration . A significantly higher efficiency was reported for the sulfur-containing S/Ag-TiO 2 @g-C 3 N 4 material, which decreases the initial TCS concentration by approximately 92% under the above-mentioned conditions .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus, incorporating doped TiO 2 with g-C 3 N 4 structures has also attracted great attention for the degradation of CECs. For instance, S-Ag/TiO 2 @g-C 3 N 4 [102] was employed for the degradation of Triclosan (TS) and yielded 92.3% degradation of TS within 60 min. under visible light irradiation.…”
Section: Tio 2 /G-c 3 Nmentioning
confidence: 99%